2021
DOI: 10.1021/acsami.1c12008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Protein Corona on Precoated Protein Nanoparticles and Determined Nanoparticles with Ultralow Protein Corona and Efficient Targeting in Vivo

Abstract: The protein corona on nanoparticles (NPs) is a critical problem that often screens the targeting molecules and becomes one of the key reasons for the lack of practical application in nanotherapy. It is critical to fully understand the mechanism of the nanoparticle–biological interactions to design the nanoparticle-based therapeutic agents. Some types of proteins can be precoated on the nanoparticles to avoid unwanted protein attachment; however, the ultralow level of protein corona is hard to achieve, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…For instance, Zhong et al synthesized nanoparticles with precoated proteins by applying 1-ethyl-3-(3-(dimethylamino)propyl)-carbodiimide/ N-hydroxysuccinimide (EDC/NHS) chemistry between the exposed carboxylic groups of the starch-coated poly(methyl methacrylate-co-acrylic acid) nanoparticles (St NPs) and the primary amino groups of various proteins. 25 The antifouling behavior of the St NPs was found to be strongly dependent on the interaction energy between the precoated protein and serum protein pair. The minimal corona formation observed in casein-precoated St NPs was attributed to the highest interaction energy and minimal hydrogen-bonding formation.…”
Section: Chemical Signatures Of the Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, Zhong et al synthesized nanoparticles with precoated proteins by applying 1-ethyl-3-(3-(dimethylamino)propyl)-carbodiimide/ N-hydroxysuccinimide (EDC/NHS) chemistry between the exposed carboxylic groups of the starch-coated poly(methyl methacrylate-co-acrylic acid) nanoparticles (St NPs) and the primary amino groups of various proteins. 25 The antifouling behavior of the St NPs was found to be strongly dependent on the interaction energy between the precoated protein and serum protein pair. The minimal corona formation observed in casein-precoated St NPs was attributed to the highest interaction energy and minimal hydrogen-bonding formation.…”
Section: Chemical Signatures Of the Proteinmentioning
confidence: 98%
“…Numerous studies have exploited surface-modification chemistries to elucidate the mechanisms of protein–protein and nanomaterial–protein interactions. For instance, Zhong et al synthesized nanoparticles with precoated proteins by applying 1-ethyl-3-(3-(dimethylamino)­propyl)-carbodiimide/ N -hydroxysuccinimide (EDC/NHS) chemistry between the exposed carboxylic groups of the starch-coated poly­(methyl methacrylate- co -acrylic acid) nanoparticles (St NPs) and the primary amino groups of various proteins . The antifouling behavior of the St NPs was found to be strongly dependent on the interaction energy between the precoated protein and serum protein pair.…”
Section: Chemical Signatures Of the Protein Coronamentioning
confidence: 99%
“…In recent decades, nanoparticles (NPs) have gained significant attention as a versatile tool for drug delivery and disease diagnosis. , However, the inconsistent results observed in vitro and in vivo have posed significant challenges for translational studies, mainly due to the complex fate of NPs in vivo . , NPs tend to nonspecifically adsorb proteins in biological fluids, leading to the formation of a protein corona (PC), which can significantly affect their biological behavior and therapeutic efficacy. PC may endow NPs brand new physical and chemical properties causing diverse biological reactions in the body . For instance, when exposed to plasma proteins, NPs typically develop a PC that can increase the particle size by 20–40 nm .…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, we previously demonstrated that the casein coated nanoparticle has an excellent antifouling property (ultra-low protein corona) due to the high interaction energy of the casein–serum protein pair and the small number of hydrogen bond formations between them. 19 The antifouling properties of nanoparticles will avoid the deposition of complement proteins on the surfaces, which could avoid inducing strong complement activation and extend the blood circulation time. 20…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, we previously demonstrated that the casein coated nanoparticle has an excellent antifouling property (ultra-low protein corona) due to the high interaction energy of the casein-serum protein pair and the small number of hydrogen bond formations between them. 19 The antifouling properties of nanoparticles will avoid the deposition of complement proteins on the surfaces, which could avoid inducing strong complement activation and extend the blood circulation time. 20 Although the ultrasmall AuNCs have many advantages for biological applications, the enthalpic limit for a spherical nanoparticle occurs at a size of about 30 nm, indicating that nanoparticles smaller than this limit will not be able to drive the membrane-wrapping process effectively.…”
Section: Introductionmentioning
confidence: 99%